The operation of international law in the Russian legal system : a changing approach - Marochkin, S. I͡U. (Sergeĭ I͡Urʹevich) (Brill's Asian law series, 2019)
"This book addresses the increased role and standing of international law in the Russian legal system through analysis of judicial practice since the adoption of the Russian Constitution in 1993. The issue of interaction and hierarchy between international and domestic law within the Russian Federation is studied, combining theoretical, legal and institutional elements. Sergey Marochkin explores how methods for incorporating and implementing international law (or reasons for failing to do so) have changed over time, influenced by internal and global policy. The final sections of the book are the most illustrative, examining how 'the rule of law' remains subordinate to 'the rule of politics', both at the domestic and global level."